TRPV1 neurons regulate β-cell function in a sex-dependent manner - Joey Bou Karam; Weikang Cai; Rowaida Mohamed; Tianwen Huang; Lingqiong Meng; Erica Paige Homan; Ercument Dirice; C. Ronald Kahn; Abdelfattah El Ouaamari (Elsevier, 2018)
There is emerging evidence to support an important role for the transient receptor potential vanilloid type 1 (TRPV1) sensory innervation in glucose homeostasis. However, it remains unknown whether the glucoregulatory action of these afferent neurons is sex-biased and whether it is pancreatic β-cell-mediated. Objective: We investigated in male and female mice whether denervation of whole-body or pancreas-projecting TRPV1 sensory neurons regulates adult functional β-cell mass and alters systemic glucose homeostasis. Methods: We used a combination of pharmacological and surgical approaches to ablate whole-body or pancreatic TRPV1 sensory neurons and assessed islet β-cell function and mass, aspects of glucose and insulin homeostasis, and energy expenditure. Results: Capsaicin-induced chemodenervation of whole-body TRPV1 sensory neurons improved glucose clearance and enhanced glucose-stimulated insulin secretion without alterations in β-cell proliferation and mass, systemic insulin sensitivity, body composition, and energy expenditure. Similarly, denervation of intrapancreatic TRPV1 afferents by pancreas intraductal injection of capsaicin or surgical removal of the dorsal root ganglia projecting into the pancreas lowered post-absorptive glucose levels and increased insulin release upon glucose stimulation. The beneficial effects of TRPV1 sensory denervation on glucose tolerance and β-cell function were observed in male but not female mice. Conclusion: Collectively, these findings suggest that TRPV1 neurons regulate glucose homeostasis, at least partly, through direct modulation of glucose-induced insulin secretion and that this regulation operates in a sex-dependent manner. Keywords: TRPV1 sensory innervation, Glucose homeostasis, β-cell function, Sex difference